Atmospheric Controls on Mineral Dust Emission From the Etosha Pan, Namibia: Observations From the CLARIFY‐2016 Field Campaign. Issue 14 (13th July 2021) - Clements, Matthew; Washington, Richard
Abstract: This paper presents meteorological observations from the Etosha Pan, an ephemeral lake bed in northern Namibia that is a major source of mineral dust. The pan was instrumented during August and September 2016 as part of the CLoud‐Aerosol‐Radiation Interactions and Forcing: Year 2016 (CLARIFY‐2016) field campaign, with a Doppler lidar and Davis weather station providing detailed measurements of the boundary layer and surface winds at Etosha. A low‐level jet (LLJ) is observed on >90% of mornings during the observation period, with mean core wind speeds of ≈12 m s −1 recorded between 06:00 and 08:00. The LLJ is eroded with the onset of surface heating, and momentum is mixed‐down from the core, producing peak surface winds between 09:00 and 11:00. This process is responsible for driving dust emission from the pan, with all six dust events recorded during the observation period triggered in the hours following LLJ breakdown. Wind speeds in the core of the LLJ are significantly stronger on dust days compared to non‐dust days, hence producing stronger morning surface winds. Dust emission is synoptically modulated, with ridging of the South Atlantic Anticyclone (SAA) enhancing the pressure gradient across southern Africa and driving a stronger easterly flow at Etosha. Key features of the LLJ are represented well in ERA5, however ERA‐Interim underestimates core wind speeds by >2 m s −1 at 00:00 and by >3 m s −1 at 06:00. Both reanalyses struggle to capture the timing of LLJ onset and breakdown, with the LLJ too quick to develop during the evening transition, and too quick to erode through the morning hours. Key Points: Dust emission from one of the Southern Hemisphere's largest sources of dust is driven by the mixing‐down of momentum from a low‐level jet Lidar observations from the winter of 2016 show that a jet is present on >90% of mornings, with core wind speeds peaking between 06:00 and 08:00 Low‐level jet strength is modulated by ridging of the South Atlantic Anticyclone which enhances the pressure gradient across southern Africa